Aphelonotus schuhi sp. nov., the first species of the family Pachynomidae from Puerto Rico (Hemiptera: Heteroptera) - Kment, Petr; Rédei, Dávid (Zootaxa, 2020)
Aphelonotus schuhi sp. nov. (Hemiptera: Heteroptera: Pachynomidae: Aphelonotinae) is described from Puerto Rico based on a single male collected by flight interception trap. The new species is morphologically similar to A. taino Schuh, Weirauch & Grillo, 2015 and A. xenos Schuh, Weirauch & Grillo, 2015, being distinguished from them by the combination of the presence of a stout subapical spine on the protibia and the characteristic shape of the parameres. An informal A. xenos species-group is proposed to accommodate these three species.